The University of Évora's Participation in QA@CLEF-2007 - Saias, José (2009)
This paper presents the latest version of Senso Question Answer (QA) System, from Departamento de Informática da Universidade de Évora. This QA system uses an ontology with semantic information to support some operations. The full text collection is indexed and for each question a search is performed for documents that may have one answer. There is an ad-hoc module and a logic-programming based module that look for answers. The solution with the highest weight is then returned. The results indicate that the system is more suitable for the definition question type.